The indirect economic impact of rail freight transport: An input–output case study for Belgium. Issue 2 (June 2022) - Meersman, Hilde; Sys, Christa; Troch, Frank; Van de Voorde, Eddy; Vanelslander, Thierry
Highlights: The modal share of rail freight transport has shown little movement during the past years, despite the policy efforts. This paper is studying its direct and indirect economic impact on the Belgian national economy. The research outcome is an adapted input–output table with a detailed 'rail freight transport' sector. It is no surprise that strong links with other transportation sectors exist. In addition, a Leontief multiplier is calculated. The study reveals a potentially high total effect on the national economy. Abstract: The modal share of rail freight transport has shown little movement during the past years, despite the policy efforts made. This raises the question if intermodality should be really considered a strength for rail freight transport development. In order to make a strong case for future development decisions on rail freight transport, this paper is studying its direct and indirect economic impact on the Belgian national economy. It adapts the existing input–output methodology by distilling the rail freight sector from the existing general combined 'public and freight land transport sector' within the national calculations of the Belgian input–output table, performed by the Federal Planning Office every five years. The methodology is developed by adopting a set of assumptions, necessary to overcome data limitations, and with the collection of relevant customer and supplier data from the largest Belgian rail freight operator, holding a market share of over 85%. The outcome of the research is an adapted input–output table with a detailed 'rail freight transport' sector, highlighting the different economic relationships with the original sectors of the national input–output table. It is no surprise that strong links with other transportation sectors exist. In addition, a Leontief multiplier is calculated, approximating the total economic effect in terms of monetary units, when the output demand in the investigated rail freight sector is increased by one of this monetary unit. The study reveals a potentially high total effect on the national economy.